Wrongful Conviction in England and Wales: An Assessment of Successful Appeals and Key Contributors - Helm, Rebecca (The Wrongful Conviction Law Review)

(untitled) (University of Alberta Library, 2022)
This paper presents an analysis of 88 criminal convictions that have since been quashed on the basis of error of fact (wrongful convictions) that have occurred in England and Wales since 2007, in the context of wider set of 389 wrongful convictions that have occurred in England and Wales since 1970. Based on this analysis, three key contributors of concern are identified as having been influential in leading to wrongful convictions recently - digital evidence, guilty pleas, and misleading testimony. Cases involving each of these factors are discussed, including cases from the Post Office Scandal, which make up many of the identified wrongful convictions during this period. In considering each factor, failings in the criminal justice system that leave defendants vulnerable to wrongful conviction are discussed. The paper concludes with brief initial suggestions for reform to provide greater protection against highlighted vulnerabilities.